Silicon Valley Cybersecurity Conference Third Conference, SVCC 2022, Virtual Event, August 17-19, 2022, Revised Selected Papers - Bathen, Luis; Saldamli, Gokay; Sun, Xiaoyan; Austin, Thomas H.; Nelson, Alex J. (Communications in Computer and Information Science, 2022)
This open access book constitutes refereed proceedings of the Third Conference on Silicon Valley Cybersecurity Conference, SVCC 2022, held as virtual event, in August 17-19, 2022. The 8 full papers included in this book were carefully reviewed and selected from 10 submissions. The contributions are divided into the following thematic blocks: Malware Analysis; Blockchain and Smart Contracts; Remote Device Assessment. This is an open access book.